2003
DOI: 10.1088/0952-4746/23/1/304
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the linear no-threshold discussion

Abstract: The paper approaches the linear no-threshold (LNT) hypothesis, currently used as the basis for recommendations in radiological protection, from the point of view of the radiation mechanism. All considerations of the validity of the LNT hypothesis based on experiment or epidemiology are dismissed because of the impossibility of deriving statistically significant data at very low doses. Instead, the LNT hypothesis is assessed from a consideration of the mechanism of radiation action. The DNA double-strand break … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 150 publications
1
6
0
Order By: Relevance
“…In addition to the molecular and cellular effects, especially more information on the radiation-induced carcinogenesis process in tissues and organs is needed to fill in the gap. The current uncertainties in observed doseeffect relationships support a conservative approach that is in agreement with the current scientific knowledge [20], i.e. a linear non-threshold dose-effect relationship.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition to the molecular and cellular effects, especially more information on the radiation-induced carcinogenesis process in tissues and organs is needed to fill in the gap. The current uncertainties in observed doseeffect relationships support a conservative approach that is in agreement with the current scientific knowledge [20], i.e. a linear non-threshold dose-effect relationship.…”
Section: Discussionsupporting
confidence: 78%
“…From laboratory studies it is concluded that it is not practical to obtain information on radiation effects at doses much below approximately 20 mGy for chromo- Although from mechanistic arguments it may be inferred that the dose-response for radiation carcinogenesis has a positive slope from zero dose [20], the exact shape of the risk function at lower doses cannot be determined directly and thus has to be derived from extrapolation from observed risks at higher doses. Laboratory experiments and animal studies have provided information on the different shapes of dose-effect relationships to be used for extrapolation.…”
Section: Somatic Stochastic Effects (Carcinogenesis)mentioning
confidence: 99%
“…Epidemiological studies on lung cancer risk suggest that in cases of protracted exposures the crucial quantity for cellular radiation eff ects is the dose per cell cycle (Chadwick et al 2003). While the number of cells hit increases with the average tissue or organ dose, the average dose received by the traversed cells remains constant until multiple alpha particle hits start playing a greater role.…”
Section: Adaptive Responsementioning
confidence: 99%
“…Hence, the development and application of mechanistic models of radiation carcinogenesis seems to be a promising avenue. However, mechanistic risk models are either based on the study of alpha tracks or on exact microdosimetric quantities, like cellular doses or alpha-hit frequencies (Klebanov et al 1993, Crawford-Brown and Hofmann 2002, Chadwick et al 2003. In case of inhalable radioisotopes, such as radon or thoron progenies, these parameters can be obtained through the application of lung deposition and dosimetry models.…”
Section: Introductionmentioning
confidence: 99%